1985
DOI: 10.1200/jco.1985.3.11.1486
|View full text |Cite
|
Sign up to set email alerts
|

A prospective evaluation of 5-fluorouracil plus cisplatin in advanced squamous-cell cancer of the head and neck.

Abstract: Recent studies have shown improved efficacy of chemotherapy in patients with advanced squamous-cell cancer of the head and neck. Our purpose was to evaluate prospectively the activity of cisplatin plus 5-fluorouracil (5FU) in 37 patients with advanced stage IV squamous-cell cancer of the head and neck. There were two groups. Group 1 consisted of 19 previously untreated patients with either T4 or N3 disease. They received 100 mg/m2 cisplatin (days 1 and 28) and 120-hour infusion of 1,000 mg/m2/24 hours 5FU (day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

1987
1987
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(8 citation statements)
references
References 9 publications
0
7
0
1
Order By: Relevance
“…The drug was administered intratumorally by Squamous cell 32 12 3 13 2 2 carcinoma Adenocarcinoma 36 21 3 2 3 7 Melanoma 9 -2 5 1 1 Chordoma 2 Cisplatin as a single agent or in combination with other cytotoxic agents has significant activity in many solid tumors, particularly head and neck cancer. [23][24][25][26] There is evidence to support a dose-response relationship for this drug in sensitive tumors. However, attempts to increase dose intensity have been limited by the attendant toxicity, commonly nephrotoxicity, peripheral neuropathy, ototoxicity, myelosuppression, and electrolyte and magnesium wasting.…”
Section: Discussionmentioning
confidence: 99%
“…The drug was administered intratumorally by Squamous cell 32 12 3 13 2 2 carcinoma Adenocarcinoma 36 21 3 2 3 7 Melanoma 9 -2 5 1 1 Chordoma 2 Cisplatin as a single agent or in combination with other cytotoxic agents has significant activity in many solid tumors, particularly head and neck cancer. [23][24][25][26] There is evidence to support a dose-response relationship for this drug in sensitive tumors. However, attempts to increase dose intensity have been limited by the attendant toxicity, commonly nephrotoxicity, peripheral neuropathy, ototoxicity, myelosuppression, and electrolyte and magnesium wasting.…”
Section: Discussionmentioning
confidence: 99%
“…Higher response rates have been reported using the combination of cisplatin and 5-FU, but reported response rates with this combination have varied significantly. 5,7 Clinical assessment of response with both physical examination and radiologic evaluation is known to be difficult in these patients, which may partly account for the variability in response rates. Because median survival has not been significantly impacted despite the high reported response rates with different combinations, other outcomes, such as the proportion of patients surviving at 1 and 2 years and the response duration, may provide intermediate surrogates for treatment efficacy in this difficult clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 The combination of cisplatin and 5-fluorouracil (5-FU) is considered the standard, with reported response rates varying from 11% to 80% but without a demonstrable impact on survival. [5][6][7][8] Paclitaxel 250 mg/m 2 given as a 24-hour infusion has demonstrated clinical activity in patients with advanced SCCHN, with a single-agent response rate of 40% (4 complete and 8 partial responses in 30 patients). 9 Experimentally, it has been shown that paclitaxel can induce p53-independent apoptosis in tumor cells; 10 this is a noteworthy feature because the majority of head and neck cancers develop p53 mutations.…”
mentioning
confidence: 99%
“…The group included 31 men and 6 women with a medium age of 54 ) and a performance status of 80 (60-90). Primary sites were nasopharynx (13), oropharynx (5), hypopharynx (3), sinus (3), ethmoids (2), tongue (2), floor of the mouth (2), larynx (6) and unknown (1). 25 patients received 3 cycles of induction therapy whereas 22 completed the whole treatment programme.…”
mentioning
confidence: 99%